Analysis of the Influence of Regional Original Income, General Allocation Funds, Profit Sharing Funds and Budget Calculations Remain on the Oportunistic Behavior of Budgets - Darmawan Fadly Dalimunthe (International Journal of Applied Finance and Business Studies, 2021)
The purpose of this research to investigate and to analyze the influence of Regional Own Revenue, General Allocation Fund, Profit Sharing Fund, and Financing Surplus for Opportunistic Behavior of Budgeting. The population of this research is Regency/City Administration in North Sumatra Province. The analyze method that is used in this research are descriptive statistical analysis, the classical assumption test, multiple regression analysis, and hypothesis testing. The independent variables used in this research are Regional Own Revenue, General Allocation Fund, Profit Sharing Fund, and Financing Surplus, the dependent variable is the Opportunistic Behavior of Budgeting. The population of this research are 33 Regency/City by using purposive sampling, 15 Regency/City in year 2011 up to year 2014 were chosen as samples. This research utilizes secondary data. The result of this research show that simultaneously Regional Own Revenue, General Allocation Fund, Profit Sharing Fund, and Financing Surplus effect on the Opportunistic Behavior of Budgeting. Partially, the Regional Own Revenue and Profit Sharing Fund variable does not effect on the Opportunistic Behavior of Budgeting, meanwhile the General Allocation Fund and Financing Surplus variable has a positive significant effect on the Opportunistic Behavior of Budgeting at Regency/City in North Sumatra Province